Pulmonary Alveolar Proteinosis and new therapeutic concepts - Rodriguez Gonzalez, Claudio; Schevel, Hannah; Hansen, Gesine; Schwerk, Nicolaus; Lachmann, Nico (Klinische Pädiatrie, 2024)
Pulmonary alveolar proteinosis (PAP) is an umbrella term used to refer to a pulmonary syndrome which is characterized by excessive accumulation of surfactant in the lungs of affected individuals. In general, PAP is a rare lung disease affecting children and adults, although its prevalence and incidence is variable among different countries. Even though PAP is a rare disease, it is a prime example on how modern medicine can lead to new therapeutic concepts, changing ways and techniques of (genetic) diagnosis which ultimately led into personalized treatments, all dedicated to improve the function of the impaired lung and thus life expectancy and quality of life in PAP patients. In fact, new technologies, such as new sequencing technologies, gene therapy approaches, new kind and sources of stem cells and completely new insights into the ontogeny of immune cells such as macrophages have increased our understanding in the onset and progression of PAP, which have paved the way for novel therapeutic concepts for PAP and beyond. As of today, classical monocyte-derived macrophages are known as important immune mediator and immune sentinels within the innate immunity. Furthermore, macrophages (known as tissue resident macrophages (TRMs)) can also be found in various tissues, introducing e. g. alveolar macrophages in the broncho-alveolar space as crucial cellular determinants in the onset of PAP and other lung disorders. Given recent insights into the onset of alveolar macrophages and knowledge about factors which impede their function, has led to the development of new therapies, which are applied in the context of PAP, with promising implications also for other diseases in which macrophages play an important role. Thus, we here summarize the latest insights into the various forms of PAP and introduce new pre-clinical work which is currently conducted in the framework of PAP, introducing new therapies for children and adults who still suffer from this severe, potentially life-threatening disease.
Keywords: Macrophage; Immunity; Lung; Proteinosis